Performance Analysis on a Power and Ejector-Refrigeration System and the Involved Ejector - Zhang, Xiaolin; Deng, Shuai; Zhao, Li; Su, Wen; Xu, Weicong (Frontiers in Energy Research, 2019)
In order to make better use of the thermal energy at low and medium temperature and improve the organic Rankine cycle performance, the power, and ejector-refrigeration system has been put forward and a lot of research has been carried out. This article presents a new study of the combined system and the key component ejector using the zeotropic mixture R134a/R123 as working fluid. First, the influence of heat source temperature, turbine outlet pressure, and different mixture compositions on the performance of the combined system and ejector were analyzed. It can be found that entrainment ratio is not sensitive to the change of heat source temperature. Through exergy analysis of the combined system, it can be found that ejector, evaporator, and condenser take up for most exergy destruction of the system. The result illustrate that exergy destruction mainly occurs in the component of ejector, which can reach 50.28%. Then, the relationship between input heat of ejector, net power change value and power saved by ejector was compared. It can be found that net power reduction is less than power saved by ejector and refrigeration output. Finally, the exergy efficiency of ejector was defined and the effects of other parameters on it are analyzed. The results show that the exergy efficiency of ejector and COP are oppositely changing.